Influences of Extreme Events on Water and Carbon Cycles of Cropland Ecosystems: A Comprehensive Exploration Combining Site and Global Modeling. Issue 11 (18th November 2021) - Xia, Ye; Fu, Congsheng; Wu, Haohao; Wu, Huawu; Zhang, Haixia; Cao, Yang; Zhu, Zichun
Abstract: Climate warming increases the frequencies of drought and excessive precipitation, and the influencing mechanisms and magnitudes of these extreme events on the water and carbon cycles of different crops still remain unclear. In this study, single‐point simulations for six irrigated and rain‐fed crops and global simulation were combined to comprehensively investigate the impacts of drought and excessive precipitation on evapotranspiration (ET), irrigation, net ecosystem exchange (NEE), and yields of crops. Results illustrated that the AgroIBIS‐based CLM5 simulated ET and NEE dynamics well for rice, corn, winter wheat, soybeans, sugar beets, and potatoes after parameter optimization. The impacts of abnormal precipitation on ET, NEE, and crop yield were larger at rain‐fed sites than at irrigated sites. The influencing magnitudes of precipitation shortage on ET depended on the occurring time of drought events relative to the growth stages of crops. Precipitation shortage (excessive precipitation) reduced (increased) ET and net carbon uptake by 4%–19% (4%–7%) and 3%–15% (1%–6%) compared to normal precipitation years at irrigated sites, while corresponding decrease (increase) was 7%–35% (24%–27%) and 19%–48% (12%–34%) at rain‐fed sites. The proportional influencing magnitudes of precipitation shortage on ET, NEE, and yield increased sequentially for rain‐fed crops. At the global scale, the simulated theoretical irrigation in extremely dry years was 25%–75% larger than that in normal precipitation years, and the actual irrigation was 3.5–4.0 times as large as the simulated theoretical value at irrigated sites, implying that drought intensified water resource shortage through excessive irrigation besides precipitation shortage. Key Points: CLM5 simulated evapotranspiration (ET) and net ecosystem exchange (NEE) dynamics well for six crops, including the newly added rice Influencing magnitudes of precipitation shortage on ET and NEE are clearly affected by the occurring time of drought in the growing season The proportional influencing magnitudes of precipitation shortage on ET, NEE, and yield increased sequentially for rain‐fed crops